Neuroprotective Properties of Some Indian Medicinal Plants - Pandit, Manish K (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The study of antioxidants has gained great attraction recently due to their health implications. The central nervous system is vulnerable to oxidative stress as a consequence of high metabolic rate and deficient antioxidant system. The increasing amount of experimental evidence shows the involvement of reactive oxygen species in neurodegenerative diseases. Antioxidants neutralize free radicals and are effective in suppressing or preventing these disorders. Ayurveda, an ancient system of Indian medicine, has defined a number of plants with therapeutic benefits for the treatment of neurodegenerative disease, having antioxidant activities. Extracts of Bacopa monniera had proved to improve human cognitive function. Bacopa extract is claimed to have antioxidative function. Ginkgo biloba is reported to reduce free radical levels. Extracts of Withania somnifera improves antioxidant status in oxidative stress induced neurodegeneration. It has been proved that consumption of antioxidant rich diet may reduce lipid peroxide and increase antioxidant levels in plasma. There are still a large number of plants that need to be examined for their potential neuroprotective properties. Assays based on genomics and proteomics are expected to offer comprehensive information about molecular mechanism of neurological ailments and their protection by plant extracts. This will greatly help in identifying more potent compounds with potential applications in prevention of human ailments. Key words: Antioxidants, Neurodegeneration, Neuroprotection, Oxidative Stress.